Assessing preferences of individuals with developmental disabilities using alternative stimulus modalities: A systematic review. Issue 3 (2nd May 2019) - Heinicke, Megan R.; Carr, James E.; Copsey, Catherine J.
Abstract : The purpose of this systematic review was to identify investigations comparing the efficacy of alternative modality (e.g., pictorial, verbal, video) stimulus preference assessments for individuals with developmental disabilities. We identified articles by searching peer‐reviewed journals using the PsycINFO and ERIC databases, conducting table of contents searches of common behavioral outlets, and conducting ancestral searches of recent reviews and practitioner summaries of preference assessment methodology. A total of 32 articles met our inclusion criteria. These studies were then coded across a variety of features to gain a better understanding of the efficacy of alternative format preference assessments for individuals with developmental disabilities. In addition, we reviewed this literature for the use of prerequisite‐skill assessments and contingent‐reinforcer access to further investigate the relation between these variables and the accuracy of pictorial, verbal, and video preference assessments. A variety of methodological concerns are discussed as well as suggestions for future research.